2010
DOI: 10.2169/internalmedicine.49.3724
|View full text |Cite
|
Sign up to set email alerts
|

Fabry Disease Exhibiting Recurrent Stroke and Persistent Inflammation

Abstract: We describe two cases of Fabry disease in non-blood-related Japanese men, manifesting recurrent stroke even after the start of enzyme replacement therapy. Both exhibited chronic inflammation and ocular involvement with elevated levels of serum C reactive protein prior to the onset of stroke. We, therefore, suggest the association among persistent inflammation, ocular involvement and recurrent stroke in a certain subset of Fabry disease patients. Both cases received enzyme replacement therapy with no improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…The findings of reductions in plasma GL-3 were supported by an OS which combined data for agalsidase alfa and agalsidase beta [101], and two mixed-ERT CRs [120,133].…”
Section: Resultsmentioning
confidence: 82%
“…The findings of reductions in plasma GL-3 were supported by an OS which combined data for agalsidase alfa and agalsidase beta [101], and two mixed-ERT CRs [120,133].…”
Section: Resultsmentioning
confidence: 82%
“…Notably, several clinical and laboratory findings, as the occurrence of episodic and unexplained fever in some patients with FD, and/or the increased serum levels of ESR, CRP, and α 1- and α 2-globulin (observed also in 45.8% of our patients with FD) indicate the likely occurrence of both systemic and local inflammation in this pathology [30, 31]. The activation of the inflammatory biochemical pathways in FD, as it may occur in other lysosomal storage disorders (LSDs), is probably related to secondary inappropriate activation of the immune system, in response to storage, resulting in chronic inflammation [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…These factors include smoking, obesity, lack of physical exercise, dyslipidemia, and arterial hypertension. 53 However, genetic modifiers, such as paraoxonase gene polymorphisms, 54 angiotensin promoter, and angiotensin II receptor type I gene polymorphism, interleukin-6, protein Z, 55 inflammatory factors (myeloperoxidase, C-reactive protein), 56,57 and hyperhomocysteinemia, 58,59 could also predispose a young Fabry patient to stroke. It has been suggested that the presence of factor V Leiden may be a link between FD and stroke.…”
Section: Risk Factors Of Ischemic Stroke In Fdmentioning
confidence: 99%
“…Evidence is also emerging of an age-independent association between CWMH load and cardiomyopathy in patients with FD, 66 which may relate to the risk of ischemic stroke. Other possible influences on stroke severity in FD include polymorphisms in interleukin-6, endothelial nitric oxide synthase, and protein Z 67 ; fibrinolysis and angiogenesis factors 68,69 ; elevations in serum myeloperoxidase 56 and C-reactive protein 57 ; paraoxonase gene polymorphism 54 ; and angiotensinogen promoter and angiotensinogen receptor type I. 55 The risk of stroke in FD seems, therefore, to be related to residual enzyme activity as determined by GLA mutations, as well as other genetic and epigenetic factors not yet characterized fully.…”
Section: Risk Factors Of Ischemic Stroke In Fdmentioning
confidence: 99%